2022
DOI: 10.1002/anie.202203715
|View full text |Cite
|
Sign up to set email alerts
|

Polarization‐Dependent Ultrasensitive Dynamic Wrinkling on Floating Films Induced by Photo‐Orientation of Azopolymer

Abstract: Ubiquitous surface wrinkling has been wellstudied theoretically and experimentally. How to modulate the stress state of a liquid-supported system for the unexploited wrinkling capabilities remains a challenge.Here we report a simple linearly-polarized-light illumination to spatiotemporally trigger ultrasensitive in situ dynamic wrinkling on a floating azo-film. The smart combination of the liquid substrate with photoresponsive azo-moieties leads to the light-induced ultrafast wrinkling evolution, accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…50−52 Meanwhile, it is wellknown that the phototriggered trans−cis−trans isomerization cycles of the azobenzenes in azo-polymers can convert light energy into mechanical energy, which could induce stress relaxation in the wrinkled azo film resulting in the dynamic evolution of the surface wrinkles upon light irradiation. 22,24,53,54 The azobenzenes in azo-PI exhibit an overlap between the n−π* and π−π* transition absorption bands due to electron-donating substituents, which yielded a dynamic trans−cis−trans photoisomerization of the azobenzenes upon irradiation with light. Similar to the results of the previous works, the surface wrinkles on the azo-PI/PDMS system can be controllably modulated by regulating the as-formed localized stress field with light irradiation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…50−52 Meanwhile, it is wellknown that the phototriggered trans−cis−trans isomerization cycles of the azobenzenes in azo-polymers can convert light energy into mechanical energy, which could induce stress relaxation in the wrinkled azo film resulting in the dynamic evolution of the surface wrinkles upon light irradiation. 22,24,53,54 The azobenzenes in azo-PI exhibit an overlap between the n−π* and π−π* transition absorption bands due to electron-donating substituents, which yielded a dynamic trans−cis−trans photoisomerization of the azobenzenes upon irradiation with light. Similar to the results of the previous works, the surface wrinkles on the azo-PI/PDMS system can be controllably modulated by regulating the as-formed localized stress field with light irradiation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As one type of mechanical instability, the surface wrinkle morphologies (e.g., wavelength and amplitude) of the film/substrate bilayer system can be dynamically regulated via external stimuli, such as mechanical strain, solvent, light, electric field, and temperature. Meanwhile, it is well-known that the phototriggered trans – cis – trans isomerization cycles of the azobenzenes in azo-polymers can convert light energy into mechanical energy, which could induce stress relaxation in the wrinkled azo film resulting in the dynamic evolution of the surface wrinkles upon light irradiation. ,,, The azobenzenes in azo-PI exhibit an overlap between the n−π* and π–π* transition absorption bands due to electron-donating substituents, which yielded a dynamic trans – cis – trans photoisomerization of the azobenzenes upon irradiation with light. Similar to the results of the previous works, the surface wrinkles on the azo-PI/PDMS system can be controllably modulated by regulating the as-formed localized stress field with light irradiation. ,, As shown in Figure S9, the surface wrinkles on the azo-PI/PDMS bilayer were quickly erased via visible-light irradiation within 30 s. Meanwhile, in situ AFM characterization revealed that the surface wrinkle amplitude ( A , i.e., peak-to-valley value) of the azo-PI/PDMS bilayer decreased gradually, while the wrinkle wavelength (λ) exhibited no discernible change, during light irradiation until the surface wrinkle was completely erased (Figure and Figure S10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Taking inspiration from the rich diversity of patterned surfaces found in nature, various methods for material synthesis and processing have been emerged to produce nano-and microstructures. Inspired by the abundant patterned surfaces in nature, such as imprinting, [4][5][6] and photolithography, [7][8] tailored to various practical applications. [9][10][11] Despite the potential offered by these top-down patterning technologies, their broader utilization is hindered by various challenges, including intricate fabrication procedures, elevated expenses, constraints regarding specific geometries, and the absence of dynamic regulation capabilities.…”
Section: Introductionmentioning
confidence: 99%